The correlation between Leptin Levels and Onset of Preeclampsia - Johanes C. Mose; Masrul Masrul; Netti Suharti; Roza Sriyanti (Universitas Andalas, 2020)
The purpose of this study is to find the correlation between leptin levels and the onset of preeclampsi. This study used a cross sectional comparative study design that conducted in May 2018 - April 2019 in the SMF / Obstetrics and Gynecology department of RSUP dr. M. Djamil Padang, RSUD Achmad Mochtar, RSUD Solok, RST Reksodiwiryo. We used consecutive sampling method which consists of 69 pregnant women who fulfill the inclusion and exclusion criteria. Leptin level tests were done using ELISA method. The average level of leptin in early-onset preeclampsia is found to be the highest when compared to the late-onset preeclampsia and normal pregnancy, 64.07 ± 78.27 vs. 30.46 ± 31.99 vs. 16.61 ± 24.49. This differentiation is highly significant with the ANOVA statistical test (p <0.05). There is a significant correlation between leptin levels with the onset of preeclampsia.Keywords: preeclampsia early onset, preeclampsia late onset, leptin levels